PROACTIVE MEMEFICATION AND POLITICAL CATHARSIS: HOW ONLINE HUMOR PROMPTS POLITICAL EXPRESSION AMONG SUDANESE SOCIAL MEDIA USERS - Abdelbagi, Abubakr (AoIR Selected Papers of Internet Research, 2023)
Striving to advance our understanding of how social media is used by Sudanese people to engage in politics and continue their resistance against an authoritarian regime, this study examines how online humor facilitated political expression after the December Revolution. Using thematic analysis of user-generated content posted on the Shabab Hilween Facebook page, the main social media outlet of prominent Sudanese youth content creators, this research attempts to highlight how youth-created humorous videos prompted political expression among Sudanese social media users. The findings highlight the significance of proactive memefication and templatization as an act the page owners use to generate community user-generated content. Hundreds of memefied screenshots created or appropriated by users were observed in the comment section to address unfolding political events. This begs the question of what content is essentially popular culture for Sudanese people, especially youth, who, due to years of censorship and propaganda, have no interest in mainstream media? This study discusses the role of Sudanese content creators in addressing this cultural void. The analysis also reveals how Sudanese social media users sought political catharsis and collective relief from the Shabab Hilween page’s humorous videos and the comment section.